Some Singular Properties of Bacterial Flagella, with Special Reference to Monotrichous Forms - Roberts, F. F. (1966)
Roberts, F. F., Jr. (University of Maryland, College Park), and R. N. Doetsch. Some singular properties of bacterial flagella, with special reference to monotrichous forms. J. Bacteriol. 91:414–421. 1966.—Heat (60 C for 30 min), 10 m acetamide, and 8 m urea all brought about rapid and complete dissolution of flagella from monotrichous bacteria; hence, these flagella respond similarly to those of peritrichous forms. Chloramphenicol (10(3) μg/ml) inhibited regeneration of flagella in all peritrichously flagellated cultures; however, monotrichous forms were able to regenerate their flagella in a concentration 10(2) times that required to inhibit multiplication. Peritrichous bacteria did not synthesize flagella when infected by lytic bacteriophages. In these experiments, the time from infection to lysis was sufficient for uninfected controls to resynthesize their flagella. Monotrichous bacteria, however, in all but one instance, were able to resynthesize their flagella before lysis occurred. A study of flagella resynthesis in a non-nutritive milieu indicated that only a small amount of flagellum precursor is present in any given cell. The effect of temperature on synthesis of flagella indicated that, although some bacteria multiply and are motile at a given temperature, they are unable to resynthesize their flagella at that same temperature. This strongly suggests that initial flagellum synthesis and flagellum regeneration are not necessarily identical processes.